Impact of SARS‐CoV‐2 transmission‐based precautions on inpatient management of general medical patients. Issue 5 (10th May 2022) - Stratton, Hayley; Buntine, Paul; Ng, Reginald Bo Ren; Fu, Joy Jiayu; Joshi, Neetima; Yip, Gary; Guy, Stephen; Chean, Roy; Newnham, Evan; Lau, Jillian S. Y.
Abstract: This audit reviewed the impact on access to routine medical care and adverse outcomes in patients with suspected SARS‐CoV‐2 infection managed on a 'COVID‐19' (CV) ward compared with a general medicine ward at Box Hill Hospital, Victoria. Data were collected at two time points to capture changes associated with onsite testing. We found no healthcare delays from admission to CV wards and observed faster exits from CV wards with improved testing efficiency. This critical finding is relevant as Victoria manages a third wave of infections.